Early Eocene marine microgastropods from the Zhupure Formation in Yadong, Southern Tibet, China - Li, Xin-Fa; Li, Guo-Biao; Garvie, Christopher L. (Palaeoworld, 2024)
Numerous microgastropods are reported for from the Eocene (Ypresian) Zhepure Formation in Tüna, Yadong, Southern Tibet for the first time. Although most of the shells are incompletely preserved, the following eight species of benthic microgastropods are described and illustrated: Eulimella sp., Odostomia aff. pakistanica, Monotygma aff. marcusseni, Syrnola sp., Pyramidellidae (Syrnola?) sp., Pyramidellidae indet. sp., Mathilda (Echinimathilda) cf. duogenta and the new species Turbonilla yadongensis n. sp. As little is known about Paleogene microgastropod fauna in Tibet, the occurrence here could give further information on Cenozoic biostratigraphy of Southern Tibet, the paleoenvironment and late evolutionary history of eastern Tethyan realm. Based on this study of the little-known Eocene microgastropod assemblage, we demonstrate that a shallow marine environment existed during early Eocene in the Southern Tibet.